PENGARUH TATA KELOLA DAN KEPATUHAN SYARIAH TERHADAP KECURANGAN PADA BANK UMUM SYARIAH - Sudarni, Ahmad Nur Subkhi; Puspitasari, Elen (KRISNA: Kumpulan Riset Akuntansi, 2023)
Fraud is a fraud committed by a person or an organization who has known that the fraudulent act, or is more accurately said to take advantage of all work that has been trusted by the company for their personal interests. an act of fraud or error made by a person or entity who knows that such action may result in some unfavorable impact on other individuals or entities. Fraud can be carried out by various levels from the lower level to the top management. Internal and external parties will pay attention to several factors that influence fraud in the company, especially Islamic commercial banks. This study analyze and examine the effect of sharia governance and compliance on fraud. The population used in this study is Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK) during the last five year period, namely 2017 to 2021. With a final sample of 40. The sampling method used in this study was using a purposive technique. sampling. The data analysis technique uses multiple regression analysis using the SPSS 26 program. The results of this study explain that Islamic governance, Islamic income ratios, zakat performance ratios have a positive effect on fraud. Meanwhile, the Islamic income ratio and Islamic investment ratio have no effect on fraud.